MAKNA NEGARA HUKUM DALAM PERSPEKTIF POLITIK HUKUM (Telaah Yuridis Materil dan Formil) (JURNAL HUKUM SEHASEN, 2017)
In Article 1 Paragraph 3 of the 1945 Constitution of the Republic of Indonesia (NRI) states that Indonesia is a state of law. The law is the commander, all rights and obligations between state officials and the people gets the same treatment before the law (Article 27 of the 1945 Constitution of the Republic of Indonesia). The question is whether the concept of a state of law has achieved its ideal goal towards a nation state which is prosperous inward, just based on the One Godhead, the gap between das sollen (ideal) and das sein (empirik) in the implementation of the implementation of rights and duties a country.The study of this paper is the result of literature review with the compilation of various concepts, theories concerning the relationship of the concept of legal state with the concept of legal politics. Several concepts are analyzed with the interdisciplinary approach of nationality issues, to find constructive academic answers.The finding, that it is necessary for an official policy line of a country (legal politics). Political law is seen as a formal legal subject to the state which is its material object. The integration between the relation of the material object of law and the formal object of law as a wise step towards a prosperous nation of nation is born inward, just and prosperous based on Belief in the One Supreme